Groundwater filtration by a rapid dual-media filter - Ghazali, Abdul Halim; Jusoh, Ahmad; Megat Mohd Noor, Megat Johari (1990)
The villagers of Tanjung Sepat, in the district of Kuala Langat, Selangor, had been relying on groundwater as one of the main sources of water supply, until very recently. However the water was not up to the drinkable standards because of its high turbidity and iron content. It was also objectionable in odour and taste. Field studies were carried out to determine the effectiveness of a rapid dual-media filter made up of burnt granular oil palm shells and sand to treat the water directly i.e. without any pretreatments. Besides turbidity and iron, other parameters such as nitrate, phosphate, total suspended and total dissolved solids were also monitored. The filter was found to be effective in reducing the turbidity and iron to the acceptable limit. As for some other parameters, the study indicated that other removal techniques are necessary prior to filtration. It also showed that some kinds of aeration are adequate to reduce the odour of the water.